Dose Physiologically Performing Vigorous Exercises Good for Body Over Time - Nasim Habibzadeh (International Physiology Journal, 2018)
A commentary addresses the benefits and risks of vigorous exercise over time from a physiological perspective, discussing adaptation, monitoring, and individualized recommendations.
Keywords: Vigorous Exercise